Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 664 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Oxalis tuberosa Molina", "Geometry POLYGON((-98.4375 11.867350,-98.4375 -48.224672,-35.507812 -48.224672,-35.507812 11.867350,-98.4375 11.867350))" ] } The dataset includes 664 records from 12 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0094056-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences